2017
DOI: 10.15421/021789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrobial agents on planktonic and biofilm forms of bacteria that are isolated from chronic anal fissures

Abstract: The microorganisms that are formed in biofilm cause about 60% of chronic and recurrent diseases, and as a consequence, traditional etiotropic antibacterial therapy is ineffective. Chronic anal fissures are also a disease which is caused by biofilm forms of bacteria, has a chronic course and is difficult to treat. The sensitivity of planktonic and biofilm forms of bacteria isolated from chronic anal fissures to antibacterial drugs was determined and the method of degradation of biofilm by electrophoresis for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
6
0
7
Order By: Relevance
“…The authors suggested that the microorganisms with the ability to produce biofilm biomass complicates the antimicrobial therapy and defines its chronic development. 20 The present study also proposed a similar concept as significant number of isolated organisms showed high and medium biofilm production that belonged to those patients with fistulas for >6 months duration.…”
Section: Discussionsupporting
confidence: 72%
“…The authors suggested that the microorganisms with the ability to produce biofilm biomass complicates the antimicrobial therapy and defines its chronic development. 20 The present study also proposed a similar concept as significant number of isolated organisms showed high and medium biofilm production that belonged to those patients with fistulas for >6 months duration.…”
Section: Discussionsupporting
confidence: 72%
“…Проте мікробні популяції по-різному реагують на кожну хімічну сполуку, зокрема можуть захищатися від антибактеріальних речовин завдяки здатності продукувати ензими, які знищують біоциди, завдяки зміні проникності клітинної стінки і цитоплазматичної мембрани для запобігання потрапляння біоциду всередину (Augustin, Ali-Vehmas, & Atroshi, 2004Römling, & Balsalobre, 2012. Також один із біологічних механізмів захисту мікробних клітин від дії біоцидів -це їх здатність формувати біоплівки (Kozlovska et al, 2017;Kukhtyn et al, 2019). Мікробна біоплівка -це утворення, що складається з одного або декількох видів чи родів бактерій, які прикріплені до біогенної чи абіогенної поверхні та оточені власно продукуючим екзополісахаридним матриксом (Costerton et al, 2003;Horiuk et al, 2019).…”
Section: вступunclassified
“…Поява антибіотикорезистентних штамів мікроорганізмів привела до неефективності лікування бактеріальних хвороб у тварин, збільшення захворюваності та смертності і, як наслідок, до тривалого бактеріоносійства (Kozlovska et al, 2017). У багатьох небезпечних збудників маститів (Staphylococcus aureus, Enterococcus spp., Enterobacteriaceae, Pseudomonas aeruginosa, Acinetobacter spp., Mycobacterium tuberculosis) відзначається "ескалація" розвитку резистентності.…”
Section: вступunclassified